Near field communication with Android cookbook : discover the endless possibilities of using Android NFC capabilities to enhance your apps over 50 practical recipes /: discover the endless possibilities of using Android NFC capabilities to enhance your apps over 50 practical recipes. (2014) - Subtil, Vitor
No abstract available